Intravitreal Dexamethasone in the Management of Delayed-Onset Bleb-Associated Endophthalmitis - David J. Jacobs; Avinash Pathengay; Harry W. Flynn; Theodore Leng; Darlene Miller; Wei Shi (International Journal of Inflammation)
Purpose. To report the visual acuity (VA) outcomes and culture results of delayed-onset bleb-associated endophthalmitis (BAE) with and without intravitreal dexamethasone (IVD). Methods. Retrospective nonrandomized comparative case series of BAE at Bascom Palmer Eye Institute between January 1, 1996 and December 31, 2009. Clinical data were compared using the 2-sided Student's t-test for patients who received IVD and patients who did not receive IVD. Results. 70/83 (84%) received IVD, and 13/83 (16%) did not receive IVD. Mean baseline VA was 20/90 in the IVD group and 20/70 in the group that did not receive IVD (P=0.57). Mean presenting VA was 0.9/200 in the IVD group and 1.7/200 in the group that did not receive IVD (P=0.23). Repeat cultures were positive in 2/70 (3%) IVD cases and 1/13 (8%) cases that did not receive IVD (P=0.57). Mean VA at 1 month was 5/200 in the IVD group and 1.8/200 in the group that did not receive IVD, logMARΔ of 0.85 and 1.56, respectively (P=0.02). Mean VA at 3 months was 7/200 in the IVD group and 3/200 in the group that did not receive IVD, logMARΔ of 0.74 and 1.33, respectively (P=0.14). Conclusion. In the current study of BAE, IVD was associated with improved short-term VA outcomes without an increased rate of persistent infection.